Deepening Decentralised Governance in Rural India: Lessons from the People's Plan Initiative of Kerala - M.A. Oommen (CSESWP11, 2004)
Despite over more than half a century of the Indian republic, governance in rural India has failed to improve the quality of life of the average villager. He/She continues to live as the victims of innumerable unfreedoms. That Kerala has out distanced the rest of India in terms of its social and human development attainments is now fairly well acknowledged in the development literature and among policy makers throughout the world. The 73rd Constitutional Amendment is a great initiative to establish `institutions of local self government' with the task to prepare and implement `plans for economic development and social justice'. Responding to this amendment Kerala has launched in mid-1996 a unique decentralized planning experiment to enhance participatory democracy and quality of life of the local people. This paper is a critique of this experiment to draw lessons for the other Indian states (which still lag way behind Kerala) and for Kerala State itself to put decentralization and democratic practices on a sound and stable footing